2020
DOI: 10.1088/1361-6528/ab5bc5
|View full text |Cite
|
Sign up to set email alerts
|

g-C3N4/Pt/BiVO4 nanocomposites for highly efficient visible-light photocatalytic removal of contaminants and hydrogen generation

Abstract: Inspired by natural photosynthesis, artificial heterojunction photocatalysts have been extensively studied. Herein, a novel ternary graphitic carbon nitride/platinum/bismuth vanadate (g-C3N4/Pt/BiVO4) photocatalytic system was successfully synthesized, where Pt/BiVO4 nanosheet is anchored on the surface of layered g-C3N4, as evidenced by structural observations. Ultraviolet photoelectron spectroscopy and ultraviolet–visible diffuse reflectance spectroscopy are carried out to identify the position of the conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…To address these challenges, a composite of semiconductor photocatalytic materials and graphene systems can be used to broaden the absorption range of visible light and enhance the light absorption intensity of its materials [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Due to graphene’s metallic properties, the heterojunctions constructed are transformed into Schottky heterojunctions.…”
Section: Introductionmentioning
confidence: 99%
“…To address these challenges, a composite of semiconductor photocatalytic materials and graphene systems can be used to broaden the absorption range of visible light and enhance the light absorption intensity of its materials [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Due to graphene’s metallic properties, the heterojunctions constructed are transformed into Schottky heterojunctions.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of g-C 3 N 4 /Nb 2 O 5 production was also attributed to the direct Z-scheme due to the significant increase in hydrogen production compared to individual components under simulated solar light illumination, reduced recombination rate, and staggered band positions, as reported by Idrees et al [59]. Si et al also reported enhanced hydrogen production using g-C 3 N 4 /BiVO 4 [27]. Hydroxyl radicals were detected using terephthalic acid as the scavenger.…”
Section: Direct Z-schemementioning
confidence: 62%
“…Along with the band gap, CB can also be determined. Some examples of photocatalysts that have been analyzed in this way are g-C 3 N 4 /BiVO 4 [27] or TiO 2 [87]. Computational calculations, as first-principles density functional theory (DFT), can provide insight into the coupling interactions and electron transfer at the interface of the heterostructure.…”
Section: Charge Transfer Mechanisms: Supporting Experimental Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…32 For V 2p (Figure 4c), binding energies at around 516.6 and 517.8 eV are assigned to V 4+ and V 5+ in VO 4 3− (Figure 4c); the V 4+ can play the role of an electron sink to restrain the charges' recombination, which will be beneficial to improving the photocatalytic performance. 33 The O 1s spectrum is presented in Figure 4d; for BiVO 4 , the peaks centered at 529.8 and 531.1 eV are ascribed to the lattice oxygen (O 2− in the Bi−O band) and the oxygen in the surface hydroxyl species of the sample. 34,35 The other two peaks at 530.8 and 532.3 eV in the g-C 3 N 4 /PI sample are assigned to CO and the O in H 2 O, 35,36 respectively.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%